Redox-active polymers as promising electrodes for rechargeable lithium batteries - Xie, Jian (2018)
Electrode materials play a critical role in achieving high energy density and long cycle life rechargeable lithium batteries. The increasing concern with respect to the use of traditional inorganic electrode materials on resources and environmental issues has strongly inspired scientists to search green energy electrodes. Organic compounds are potentially sustainable and renewable materials as many of them can be obtained from natural products and biomass. To meet the ever-growing demands for the next generation versatile and sustainable energy-related devices, redox-active polymers, which have potential advantages over inorganic materials, are among the most promising types of green candidates. The properties of redox-active polymers can be tuned through the modification of the structure and incorporation of different functional moieties.